Negative electrode composite material and preparation method thereof, negative electrode pole piece and sodium ion battery
By using FeP and Fe7S8 coated cotton fiber-based carbon materials in the negative electrode materials of sodium ion batteries, the efficiency of sodium ion deintercalation channel is improved, and the problem of low capacity and low efficiency of sodium ion battery negative electrode materials is solved, achieving high Energy density and long cycle stability and reduce costs.
Patent Information
- Application Number
- CN202411258296.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The existing sodium ion battery negative electrode materials have low capacity and first-time Coulomb efficiency, making it difficult to meet the needs of high energy density and long cycle life, and lithium ion battery resources are scarce, so alternative technologies are needed.
Cotton fiber-based carbon material with FeP and Fe7S8 on the surface is used as the negative electrode material of sodium ion battery. The pore volume and active material coating of the material are increased through specific preparation methods to form an efficient sodium ion deintercalation channel.
It achieves high gram capacity, excellent first-time Coulomb efficiency and rate performance, and reduces manufacturing costs. The process adopts low-temperature calcination, which is suitable for industrial applications.
Smart Images

Figure CN119133401A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a negative electrode composite material and a preparation method thereof, a negative electrode pole piece and a sodium ion battery. Background Art
[0002] Due to the high energy density and power output, excellent safety and long cycle life of lithium-ion batteries (LIB), they are widely used in the field of new energy. It is expected that by 2030, the annual growth rate of the global grid battery energy storage market will reach 23% or even higher. However, lithium (Li) is a very limited resource in the earth's crust, containing only 0.0017wt%. With the vigorous development of the new energy field, people's demand for lithium-ion batteries is also increasing, and lithium resources are gradually in short supply, which will cause a major crisis of lithium-ion batteries in the future.
[0003] Therefore, it is necessary to focus on developing energy storage devices based on earth-abundant and sustainable elements, such as sodium-ion batteries (SIBs), which are considered to be the most suitable battery technology to replace lithium-ion batteries. Sodium (Na) is cheaper and more abundant than lithium, accounting for an estimated 2.8wt% of the total Na concentration in the earth's crust. In addition, there are many similarities between the physical and chemical properties of sodium and lithium, making Na-ion batteries a very advantageous alternative.
[0004] However, since the atomic radius of sodium (0.102nm) is much larger than that of lithium (0.076nm), this will greatly limit the transport process of sodium ions and destroy the structural stability of the material during the charge and discharge cycle. Therefore, the negative electrode material of sodium ion batteries requires a larger interlayer spacing to accommodate the diffusion and transport of sodium ions. At present, hard carbon is the mainstream negative electrode material for sodium ion batteries. The gram capacity and first coulomb efficiency of conventional hard carbon are poor. Therefore, it is urgent to develop high-performance sodium ion battery negative electrode materials with high gram capacity and high first coulomb efficiency. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a negative electrode composite material and a preparation method thereof, a negative electrode pole piece and a sodium ion battery. The negative electrode composite material provided by the present invention contains a high pore volume, can serve as a channel for sodium ion deintercalation, and exhibits high gram capacity and high first coulombic efficiency as a negative electrode material for a sodium ion battery.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a negative electrode composite material, comprising a cotton fiber-based carbon material containing FeP and Fe7S8 on the surface.
[0008] The negative electrode composite material provided by the present invention contains a high pore volume, can serve as a channel for sodium ion deintercalation, and exhibits high gram capacity and high first coulombic efficiency as a negative electrode material for a sodium ion battery.
[0009] Furthermore, the negative electrode composite material includes a cotton fiber-based carbon material and FeP and Fe7S8 loaded on the cotton fiber-based carbon material;
[0010] And / or, the negative electrode composite material is a sodium ion battery negative electrode composite material;
[0011] And / or, in the negative electrode composite material, the mass fraction of FeP is 5% to 20%, and the mass fraction of Fe7S8 is 5% to 30%;
[0012] And / or, the FeP is obtained by reacting a cotton fiber-based carbon / Fe3C composite material with a phosphorus source, the Fe7S8 is obtained by reacting a cotton fiber-based carbon / Fe3C composite material with a sulfur source, the reaction temperature is 500-700°C, the mass ratio of the cotton fiber-based carbon / Fe3C composite material, the phosphorus source and the sulfur source is 1:(1-20):(0.5-2), and the phosphorus source includes NaH2PO2 . at least one of H2O and red phosphorus, wherein the sulfur source comprises sulfur powder;
[0013] And / or, the cotton fibers include waste cotton cloth.
[0014] In a second aspect, the present invention provides a method for preparing the negative electrode composite material as described in the first aspect, the preparation method comprising the following steps:
[0015] S1, soaking the cotton fiber in an alkaline solution, taking it out, and washing the cotton fiber with water until the pH value of the filtrate is in the range of 6-8;
[0016] S2, soaking the cotton fiber treated in step S1 in an iron compound solution, shaking, taking out and drying for later use;
[0017] S3, calcining the sample treated in step S2 under a protective gas atmosphere, and grinding to obtain a cotton fiber-based carbon / Fe3C composite material;
[0018] S4. Put the cotton fiber-based carbon / Fe3C composite material into a small crucible, and put the small crucible into a large crucible containing a phosphorus source and a sulfur source, calcine under a protective gas atmosphere, and grind to obtain the negative electrode composite material.
[0019] Furthermore, in step S1, the cotton fiber is cut into small pieces with a length and width of 4cm*4cm-6cm*6cm and immersed in the alkaline solution for 30min-60min;
[0020] and / or, in step S1, the mass of the cotton fiber is 2.5 g-3.5 g;
[0021] And / or, the base includes at least one of sodium hydroxide and potassium hydroxide;
[0022] And / or, the solid content of the alkaline solution is 10%-25%;
[0023] And / or, in step S1, after the water washing, the cotton fiber is vacuum dried at a temperature of 90-120°C for 10-15 hours.
[0024] Further, the iron-containing compound includes Fe(NO3)3;
[0025] And / or, the concentration of iron ions in the iron-containing compound solution is 0.5 mol / L-2 mol / L;
[0026] And / or, in step S2, a constant temperature oscillator is used for oscillation, the oscillation temperature is 20° C.-30° C., and the oscillation time is 8 h-24 h;
[0027] And / or, in step S2, a vacuum drying oven is used for drying, the drying temperature is 60° C.-80° C., and the drying time is 12 h-24 h.
[0028] Further, in step S3, the protective gas includes nitrogen;
[0029] And / or, in step S3, the calcination includes heating to 600-900°C at a heating rate of 2-5°C / min and keeping the temperature for 2-4h.
[0030] Further, in step S4, the phosphorus source and the sulfur source are located at different positions in the large crucible, and the stacking height of the phosphorus source and the sulfur source is not higher than the height of the small crucible;
[0031] And / or, in step S4, the volume ratio of the small crucible to the large crucible is 1:3-1:4;
[0032] And / or, the small crucible is not covered with a lid, and the large crucible is covered with a lid.
[0033] Further, in step S4, the protective gas includes nitrogen, and the calcination includes heating to 500-700° C. at a heating rate of 2-5° C. / min and keeping the temperature for 4-8 hours;
[0034] And / or, in step S4, the mass ratio of the cotton fiber-based carbon / Fe3C composite material, the phosphorus source and the sulfur source is 1:(1-20):(0.5-2).
[0035] In a third aspect, the present invention provides a negative electrode plate, the negative electrode plate comprising:
[0036] a negative electrode current collector layer; and
[0037] A negative electrode material layer is disposed on the surface of the negative electrode current collector layer, and the negative electrode material layer comprises the negative electrode composite material described in the first aspect or the negative electrode composite material prepared by the preparation method described in the second aspect.
[0038] In a fourth aspect, the present invention provides a sodium ion battery, comprising the negative electrode sheet described in the third aspect.
[0039] Compared with the prior art, the beneficial effects of the present invention include at least one of the following:
[0040] (1) The negative electrode composite material provided by the present invention contains a high pore volume, can serve as a channel for sodium ion deintercalation, and exhibits high gram capacity and high first coulombic efficiency as a negative electrode material for sodium ion batteries.
[0041] (2) The negative electrode composite material provided by the present invention exhibits good rate performance and cycle stability as a negative electrode material for sodium ion batteries.
[0042] (3) The present invention uses waste cotton commonly found in daily life as raw material, which greatly reduces the manufacturing cost.
[0043] (4) The negative electrode carbon material of the present invention is calcined under low temperature conditions after adsorbing an iron source to obtain a cotton fiber-based carbon @Fe3C material with a high degree of graphitization. The composite material is then calcined at a second low temperature to obtain a composite material with iron phosphide and iron sulfide active substances coated on the surface, which can improve the sodium storage capacity of the carbon material, thereby increasing the gram capacity of the carbon material.
[0044] (5) The carbon material is used as a substrate to provide a carbon source, and iron phosphide and iron sulfide are used as active materials to coat the surface of the carbon material, providing a high porosity and improving the ICE (first coulomb efficiency) and rate performance of the carbon material.
[0045] (6) Compared with other processes, the entire process adopts a low-temperature calcination method, which greatly reduces the synthesis cost and is conducive to industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0047] Figure 1 A flow chart of a method for preparing a negative electrode composite material provided in Example 1 of the present invention;
[0048] Figure 2 A schematic diagram of the positions of raw materials in the method for preparing the negative electrode composite material provided in Example 1 of the present invention;
[0049] Figure 3 The XRD pattern of the negative electrode composite material prepared in embodiment 1 of the present invention;
[0050] Figure 4 The cycle spectrum of the negative electrode composite material provided in Example 1 of the present invention at 2A / g;
[0051] Figure 5 SEM images of the negative electrode composite material prepared in Example 1 of the present invention at 10000 times (a) and 5000 times (b) imaging. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0053] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0054] In a first aspect, the present invention provides a negative electrode composite material, comprising a cotton fiber-based carbon material containing FeP and Fe7S8 on the surface.
[0055] The negative electrode composite material provided by the present invention contains a high pore volume, can serve as a channel for sodium ion deintercalation, and exhibits high gram capacity and high first coulombic efficiency as a negative electrode material for a sodium ion battery.
[0056] In the above-mentioned negative electrode composite material, as an optional implementation manner, the negative electrode composite material includes a cotton fiber-based carbon material and FeP and Fe7S8 coated on the surface of the cotton fiber-based carbon material.
[0057] In the above negative electrode composite material, as an optional implementation, the negative electrode composite material includes a cotton fiber-based carbon material and FeP and Fe7S8 supported on the cotton fiber-based carbon material.
[0058] In the above negative electrode composite material, as an optional implementation, the negative electrode composite material is a sodium ion battery negative electrode composite material.
[0059] In the above-mentioned negative electrode composite material, as an optional embodiment, in the negative electrode composite material, the mass fraction of FeP is 5% to 20% (for example, it can be 5%, 10%, 15% or 20%), and the mass fraction of Fe7S8 is 5% to 30% (for example, it can be 5%, 10%, 15%, 20%, 25% or 30%).
[0060] In the above-mentioned negative electrode composite material, as an optional embodiment, the FeP is obtained by reacting a cotton fiber-based carbon / Fe3C composite material with a phosphorus source, and the Fe7S8 is obtained by reacting a cotton fiber-based carbon / Fe3C composite material with a sulfur source, the reaction temperature is 500-700°C (for example, it can be 500°C, 550°C, 600°C, 650°C, 700°C), and the mass ratio of the cotton fiber-based carbon / Fe3C composite material, the phosphorus source and the sulfur source is 1:(1-20):(0.5-2) (for example, it can be 1:5:1.5, 1:10:1, 1:15:0.5).
[0061] In the above negative electrode composite material, as an optional embodiment, the cotton fiber comprises waste cotton cloth. The role of waste cotton in the negative electrode composite material provided by the present invention is firstly to serve as a carbon source, and secondly because it has a strong adsorption capacity and can uniformly adsorb Fe 3+ ; From a technological perspective, choosing waste cotton as a carbon source only requires alkali treatment of the raw materials and then calcination to generate the carbon source. The process route is simple. At the same time, waste cotton has strong adsorption properties and can adsorb active substances very well. From a production perspective, the reason for choosing it is that it has low cost, is common in life, and is easily available.
[0062] In the above-mentioned negative electrode composite material, as an optional embodiment, the phosphorus source includes NaH2PO2 . At least one of H2O and red phosphorus, preferably NaH2PO2 to improve safety . H2O.
[0063] In the above negative electrode composite material, as an optional implementation, the sulfur source includes sulfur powder.
[0064] In a second aspect, the present invention provides a method for preparing the negative electrode composite material as described in the first aspect, the preparation method comprising the following steps:
[0065] S1, soaking the cotton fiber in an alkaline solution, taking it out, and washing the cotton fiber with water until the pH value of the filtrate is in the range of 6-8;
[0066] S2, soaking the cotton fiber treated in step S1 in an iron compound solution, shaking, taking out and drying for later use;
[0067] S3, calcining the sample treated in step S2 under a protective gas atmosphere, and grinding to obtain a cotton fiber-based carbon / Fe3C composite material (the Fe3C particles are coated inside the cotton fiber-based carbon);
[0068] S4. Put the cotton fiber-based carbon / Fe3C composite material into a small crucible, and put the small crucible into a large crucible containing a phosphorus source and a sulfur source, calcine under a protective gas atmosphere, and grind to obtain the negative electrode composite material.
[0069] The invention can remove natural impurities on cotton fibers as well as slurry, oil agent and contaminated dirt on the cotton fibers during processing by soaking with an alkali solution.
[0070] In step S4, the present invention adopts a gas phase synthesis method to sublime the sulfur source and phosphorus source in the large crucible by calcination to form a gas that reacts with the composite material in the small crucible to synthesize a cotton fiber-based carbon material with a surface rich in FeP and Fe7S8.
[0071] In the above-mentioned method for preparing the negative electrode composite material, as an optional implementation, in step S1, the cotton fiber is cut into small pieces with a length and width of 4cm*4cm-6cm*6cm and immersed in the alkaline solution for 30min-60min, for example, 30min, 40min, 50min or 60min.
[0072] In the above method for preparing the negative electrode composite material, as an optional implementation, in step S1, the mass of the cotton fiber is 2.5g-3.5g, for example, 2.5g, 3g or 3.5g.
[0073] In the above method for preparing the negative electrode composite material, as an optional implementation, the base includes at least one of sodium hydroxide and potassium hydroxide.
[0074] In the above method for preparing the negative electrode composite material, as an optional implementation, the solid content of the alkaline solution is 10%-25%, for example, it can be 10%, 15%, 20% or 25%.
[0075] In the above-mentioned method for preparing the negative electrode composite material, as an optional embodiment, in step S1, after the water washing, the cotton fiber is vacuum dried at a temperature of 90-120°C (for example, it can be 90°C, 100°C, 110°C or 120°C) and a time of 10-15 hours (for example, it can be 10 hours, 11 hours, 12 hours, 14 hours or 15 hours).
[0076] In the above-mentioned method for preparing the negative electrode composite material, as an optional implementation, the iron-containing compound includes Fe(NO3)3.
[0077] In the above method for preparing the negative electrode composite material, as an optional implementation, the concentration of iron ions in the iron-containing compound solution is 0.5 mol / L-2 mol / L, for example, 0.5 mol / L, 1 mol / L, 1.5 mol / L or 2 mol / L.
[0078] In the above-mentioned method for preparing the negative electrode composite material, as an optional embodiment, in step S2, a constant temperature oscillator is used for oscillation, and the oscillation temperature is 20℃-30℃, for example, it can be 20℃, 22℃, 24℃, 26℃, 28℃ or 30℃, and the oscillation time is 8h-24h, for example, it can be 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h.
[0079] In the above-mentioned method for preparing the negative electrode composite material, as an optional embodiment, in step S2, a vacuum drying oven is used for drying, and the drying temperature is 60°C-80°C, for example, it can be 60°C, 65°C, 70°C, 75°C or 80°C, and the drying time is 12h-24h, for example, it can be 12h, 14h, 16h, 18h, 20h, 22h or 24h.
[0080] In the above method for preparing the negative electrode composite material, as an optional implementation, in step S3, the protective gas includes nitrogen.
[0081] In the above-mentioned method for preparing the negative electrode composite material, as an optional embodiment, in step S3, the calcination includes heating to 600-900°C (for example, 600°C, 700°C, 800°C or 900°C) at a heating rate of 2-5°C / min (for example, 2°C / min, 3°C / min, 4°C / min or 5°C / min), and keeping warm for 2-4h.
[0082] In the above-mentioned method for preparing the negative electrode composite material, as an optional implementation, in step S4, the phosphorus source and the sulfur source are located at different positions in the large crucible, and the stacking height of the phosphorus source and the sulfur source is not higher than the height of the small crucible. In this embodiment, by limiting the phosphorus source and the sulfur source to be located at different positions in the large crucible, it is possible to avoid the phosphorus source and the sulfur source from reacting in a molten state to generate by-products after the two are mixed.
[0083] The volume ratio of the small crucible to the large crucible can be determined according to the size of the muffle furnace space and the fit of the two crucibles. In the above-mentioned method for preparing the negative electrode composite material, as an optional embodiment, in step S4, the volume ratio of the small crucible to the large crucible is 1:3-1:4, for example, the volume of the small crucible is 30ml, and the volume of the large crucible is 100ml.
[0084] In the above method for preparing the negative electrode composite material, as an optional implementation, the small crucible is not covered with a lid, and the large crucible is covered with a lid.
[0085] In the above-mentioned method for preparing the negative electrode composite material, as an optional embodiment, in step S4, the protective gas includes nitrogen, and the calcination includes heating to 500-700°C (for example, 500°C, 550°C, 600°C, 650°C, 700°C) at a heating rate of 2-5°C / min (for example, 2°C / min, 3°C / min, 4°C / min or 5°C / min), and keeping warm for 4-8h (for example, 4h, 5h, 6h or 8h). The present invention is to sublime the phosphorus source and the sulfur source into a gas phase under high temperature conditions and composite them with a cotton fiber-based carbon material containing Fe3C. The speed of the heating rate will affect the sublimation state of the phosphorus source and the sulfur source. Different products are obtained when the calcination temperature is too high or too low, such as obtaining FeP2, FeS and other phases.
[0086] In the above-mentioned method for preparing the negative electrode composite material, as an optional implementation, in step S4, the mass ratio of the cotton fiber-based carbon / Fe3C composite material, the phosphorus source and the sulfur source is 1:(1-20):(0.5-2) (for example, it can be 1:5:1.5, 1:10:1, 1:15:0.5).
[0087] In a third aspect, the present invention provides a negative electrode plate, the negative electrode plate comprising:
[0088] a negative electrode current collector layer; and
[0089] A negative electrode material layer is disposed on the surface of the negative electrode current collector layer, and the negative electrode material layer comprises the negative electrode composite material described in the first aspect or the negative electrode composite material prepared by the preparation method described in the second aspect.
[0090] In a fourth aspect, the present invention provides a sodium ion battery, comprising the negative electrode sheet described in the third aspect.
[0091] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.
[0092] Example 1
[0093] This embodiment provides a negative electrode composite material, which includes a waste cotton cloth-based carbon material containing FeP and Fe7S8 on the surface. The mass fraction of FeP in the negative electrode composite material is 10.14%, and the mass fraction of Fe7S8 is 25.33%.
[0094] The method for preparing the negative electrode composite material provided in this embodiment comprises the following steps:
[0095] S1. Cut 3g of waste cotton cloth into small pieces of 4cm*4cm and soak them in 18% solid content NaOH solution for 30min. Meanwhile, prepare 1mol / L Fe(NO3)3 solution;
[0096] The waste cotton cloth soaked in NaOH solution was treated with deionized water, washed until the pH of the filtrate was neutral (pH value was 7), and then dried at 100°C in vacuum (vacuum degree was -0.1Mpa) for 12h.
[0097] S2. Soak the dried waste cotton cloth in 1 mol / L Fe(NO3)3 solution, use a constant temperature oscillator, keep it at 25°C for 8 hours, take it out and put it into a vacuum drying oven, dry it at 60°C in vacuum (vacuum degree is -0.1Mpa) for 12 hours for use.
[0098] S3. Calcine the waste cotton cloth dried in step S2 in a muffle furnace under a nitrogen atmosphere. During the calcination process, the temperature is increased to 700°C at a heating rate of 2°C / min, and the temperature is kept for 2 hours. Then, the waste cotton cloth is ground in an agate mortar to obtain a carbon material in which Fe3C is coated in the waste cotton cloth (waste cotton cloth-based carbon / Fe3C composite material).
[0099] S4, put the composite material prepared in step S3 into a small crucible with a volume of 30 ml, and place the small crucible on one side with NaH2PO2 . H2O and sulfur powder on one side in a large crucible with a volume of 100 ml, NaH2PO2 . The stacking height of H2O and sulfur powder is less than the height of the small crucible. The small crucible is not covered with a lid, and the large crucible is covered with a lid (such as Figure 2 As shown), where the composite material: NaH2PO2 .The mass ratio of H2O: sulfur powder is 1:5:1.5, and the calcination is carried out in a muffle furnace under nitrogen protection. During the calcination process, the temperature is raised to 600°C at a heating rate of 2°C / min, and the temperature is kept for 6 hours. Then it is cooled to the natural ambient temperature and ground in an agate mortar to obtain a waste cotton cloth-based carbon material (negative electrode composite material) rich in FeP and Fe7S8 on the surface. The specific preparation flow chart is as follows Figure 1 shown.
[0100] Figure 3 The XRD pattern of the negative electrode composite material prepared in this embodiment (XRD pattern of cotton fiber-based carbon material doped with FeP-Fe7S8) is Figure 3 It can be seen that the negative electrode composite material includes FeP and Fe7S8 phases, which proves that a composite material containing FeP and Fe7S8 has been synthesized.
[0101] Figure 4 The cycle spectrum of the negative electrode composite material provided in this embodiment at 2A / g is shown by Figure 4 It can be seen that the capacity retention rate of the negative electrode composite material is 90.45% after 480 cycles, and the current density of 0.1A / g in the first 10 cycles of charging and discharging is to activate the battery.
[0102] Figure 5 The SEM images of the negative electrode composite material prepared in this example at 10000 times (a) and 5000 times (b) imaging are shown in FIG. Figure 5 It can be seen that FeP and Fe7S8 particles are evenly distributed on the surface of waste cotton cloth.
[0103] Example 2
[0104] This embodiment provides a negative electrode composite material, including a waste cotton cloth-based carbon material containing FeP and Fe7S8 on the surface, wherein the mass fraction of FeP in the negative electrode composite material is 13.76%, and the mass fraction of Fe7S8 is 21.46%.
[0105] The preparation method of the negative electrode composite material provided in this embodiment is basically the same as that in Example 1, except that in step S1, 3g of waste cotton is cut into small pieces of 6cm*6cm, and the solid content of the NaOH solution is 10%; in step S2, it is kept at 25°C for 12h and vacuum dried for 20h; in step S4, the composite material: NaH2PO2 . The mass ratio of H2O: sulfur powder is 1:10:1.
[0106] Example 3
[0107] This embodiment provides a negative electrode composite material, including a waste cotton cloth-based carbon material containing FeP and Fe7S8 on the surface, wherein the mass fraction of FeP in the negative electrode composite material is 19.38%, and the mass fraction of Fe7S8 is 17.41%.
[0108] The preparation method of the negative electrode composite material provided in this embodiment is basically the same as that in embodiment 1, except that in step S4, the composite material: NaH2PO2 . The mass ratio of H2O: sulfur powder is 1:15:0.5.
[0109] Example 4
[0110] This embodiment provides a negative electrode composite material, including a waste cotton cloth-based carbon material containing FeP and Fe7S8 on the surface. The mass fraction of FeP in the negative electrode composite material is 7.45%, and the mass fraction of Fe7S8 is 21.21%.
[0111] The method for preparing the negative electrode composite material provided in this embodiment is substantially the same as that in embodiment 1, except that in step S4, the heating rate is 5° C. / min.
[0112] Comparative Example 1
[0113] This comparative example provides a method for preparing a negative electrode composite material, which comprises the following steps:
[0114] S1. Cut 3g of waste cotton cloth into small pieces of 4cm*4cm and soak them in 18% solid content NaOH solution for 30min. Meanwhile, prepare 1mol / L Fe(NO3)3 solution;
[0115] The waste cotton cloth soaked in NaOH solution was treated with deionized water, washed until the pH of the filtrate was neutral (pH value was 7), and then dried at 100°C in vacuum (vacuum degree was -0.1Mpa) for 12h.
[0116] S2. Soak the dried waste cotton cloth in 1 mol / L Fe(NO3)3 solution, use a constant temperature oscillator, keep it at 25°C for 8 hours, take it out and put it into a vacuum drying oven, dry it at 60°C in vacuum (vacuum degree is -0.1Mpa) for 12 hours for use.
[0117] S3. Calcine the waste cotton cloth dried in step S2 in a muffle furnace under a nitrogen atmosphere. During the calcination process, the temperature is increased to 700°C at a heating rate of 2°C / min, and the temperature is kept for 2 hours. Then, the waste cotton cloth is ground in an agate mortar to obtain a carbon material in which Fe3C is coated in the waste cotton cloth (waste cotton cloth-based carbon / Fe3C composite material).
[0118] S4, put the composite material prepared in step S3 into a small crucible with a volume of 30 ml, and place NaH2PO2 on both sides of the small crucible. . In a large crucible with a volume of 100 ml of H2O, NaH2PO2 . The stacking height of H2O is less than the height of the small crucible, the small crucible is not covered with a lid, and the large crucible is covered with a lid, wherein the composite material is: NaH2PO2 . The mass ratio of H2O is 1:20 (at this ratio, the composite material can fully react with the phosphorus source), and calcined in a muffle furnace under nitrogen protection. During the calcination process, the temperature is increased to 600°C at a heating rate of 2°C / min, kept for 6 hours, and then cooled to the natural ambient temperature. After grinding in an agate mortar, a waste cotton cloth-based carbon material with FeP rich surface is obtained.
[0119] Comparative Example 2
[0120] This comparative example provides a method for preparing a negative electrode composite material, which comprises the following steps:
[0121] S1-S3 are exactly the same as in Example 1.
[0122] S4. Put the composite material prepared in step S3 into a small crucible with a volume of 30 ml, and put the small crucible in a large crucible with a volume of 100 ml with sulfur powder on both sides, the stacking height of the sulfur powder is less than the height of the small crucible, the small crucible is not covered with a lid, and the large crucible is covered with a lid, wherein the mass ratio of the composite material: sulfur powder is 1:2 (at this ratio, the composite material can fully react with the sulfur source), and calcine in a muffle furnace under nitrogen protection. During the calcination process, the temperature is increased to 600° C. at a heating rate of 2° C. / min, and the temperature is kept for 6 hours. Then, it is cooled to the natural environment temperature, and ground in an agate mortar to obtain a waste cotton cloth-based carbon material with a surface rich in Fe7S8.
[0123] Comparative Example 3
[0124] This comparative example provides a method for preparing a negative electrode composite material, which comprises the following steps:
[0125] S1. Cut 3g of waste cotton cloth into small pieces of 4cm*4cm and soak them in 18% solid content NaOH solution for 30min. Meanwhile, prepare 1mol / L Fe(NO3)3 solution;
[0126] The waste cotton cloth soaked in NaOH solution was treated with deionized water, washed until the pH of the filtrate was neutral (pH value was 7), and then dried at 100°C in vacuum (vacuum degree was -0.1Mpa) for 12h.
[0127] S2. Soak the dried waste cotton cloth in 1 mol / L Fe(NO3)3 solution, use a constant temperature oscillator, keep it at 25°C for 8 hours, take it out and put it into a vacuum drying oven, dry it at 60°C in vacuum (vacuum degree is -0.1Mpa) for 12 hours for use.
[0128] S3. Calcine the waste cotton cloth dried in step S2 in a muffle furnace under a nitrogen atmosphere. During the calcination process, the temperature is increased to 700°C at a heating rate of 2°C / min, and the temperature is kept for 2 hours. Then, the waste cotton cloth is ground in an agate mortar to obtain a carbon material in which Fe3C is coated in the waste cotton cloth (waste cotton cloth-based carbon / Fe3C composite material).
[0129] Comparative Example 4
[0130] This comparative example provides a method for preparing a negative electrode composite material, which comprises the following steps:
[0131] S1. Cut 3g of waste cotton cloth into small pieces of 4cm*4cm and soak them in 18% solid content NaOH solution for 30min. Meanwhile, prepare 1mol / L Fe(NO3)3 solution;
[0132] The waste cotton cloth soaked in NaOH solution was treated with deionized water, washed until the pH of the filtrate was neutral (pH value was 7), and then dried at 100°C in vacuum (vacuum degree was -0.1Mpa) for 12h.
[0133] S2. Calcine the waste cotton cloth dried in step S1 in a muffle furnace under a nitrogen atmosphere. During the calcination process, heat it to 700°C at a heating rate of 2°C / min, keep it warm for 2 hours, and then cool it to the natural environment temperature. Grind it in an agate mortar to obtain a waste cotton cloth-based carbon material (hard carbon material).
[0134] Comparative Example 5
[0135] This comparative example provides a method for preparing a negative electrode composite material, which is basically the same as that of Example 1, except that step S3 in Example 1 is not included, and specifically comprises:
[0136] S1. Cut 3g of waste cotton cloth into small pieces of 4cm*4cm and soak them in 18% solid content NaOH solution for 30min. Meanwhile, prepare 1mol / L Fe(NO3)3 solution;
[0137] The waste cotton cloth soaked in NaOH solution was treated with deionized water, washed until the pH of the filtrate was neutral (pH value was 7), and then dried at 100°C in vacuum (vacuum degree was -0.1Mpa) for 12h.
[0138] S2. Soak the dried waste cotton cloth in 1 mol / L Fe(NO3)3 solution, use a constant temperature oscillator, keep it at 25°C for 8 hours, take it out and put it into a vacuum drying oven, dry it at 60°C in vacuum (vacuum degree is -0.1Mpa) for 12 hours for use.
[0139] S3, put the sample obtained in step S2 into a small crucible with a volume of 30 ml, and place the small crucible on one side with NaH2PO2 . H2O and sulfur powder on one side in a large crucible with a volume of 100 ml, NaH2PO2 . The stacking height of H2O and sulfur powder is less than the height of the small crucible. The small crucible is not covered with a lid, and the large crucible is covered with a lid (such as Figure 2 As shown), where the composite material: NaH2PO2 . The mass ratio of H2O: sulfur powder is 1:5:1.5, and the calcination is carried out in a muffle furnace under nitrogen protection. During the calcination process, the temperature is increased to 600°C at a heating rate of 2°C / min, kept for 6 hours, and then cooled to the natural ambient temperature. After grinding in an agate mortar, a waste cotton cloth-based carbon material (negative electrode composite material) with rich FeP and Fe7S8 on the surface is obtained.
[0140] Comparative Example 6
[0141] This comparative example provides a method for preparing a negative electrode composite material. The preparation method is basically the same as that of Example 1, except that in step S4, the composite material prepared in step S3 and NaH2PO2 . H2O and sulfur powder were placed in three porcelain boats at a mass ratio of 1:5:1.5, and then the magnetic boat containing sulfur powder, the magnetic boat containing NaH2PO2 were placed in sequence from upstream to downstream of the airflow. . The magnetic boat containing H2O and the magnetic boat containing the composite material were calcined under nitrogen protection. During the calcination process, the temperature was raised to 600°C at a heating rate of 2°C / min and kept for 6 hours. Then it was cooled to the natural ambient temperature and ground in an agate mortar to obtain a waste cotton cloth-based carbon material (negative electrode composite material) rich in FeP and Fe7S8 on the surface.
[0142] Performance Testing
[0143] The pore volumes of the negative electrode composite materials prepared in the examples and comparative examples were tested by physical adsorption-desorption test method (BET test method). The results are shown in Table 1.
[0144] The negative electrode composite materials prepared in the embodiment and the comparative example were respectively assembled into button batteries, and the assembly process was as follows:
[0145] Preparation of negative electrode: The negative electrode composite materials prepared in the embodiment and the comparative example were respectively used as negative electrode carbon. 0.8g of negative electrode carbon and 0.1g of super P were manually ground and mixed in an agate mortar, taken out and poured into a small centrifuge tube, and then 0.05g of CMC powder and 0.125g of SBR (solid content 40%) were added to prepare slurry by ball milling in a small ball mill. The slurry was evenly coated on copper foil and vacuum dried. The dried negative electrode sheet was sliced to obtain a 12mm negative electrode disc for standby use, and the loading amount was 1.5mg / cm 2 ;
[0146] Preparation of electrolyte: 1.0M sodium hexafluorophosphate in DME = 100 Vol% mixed solution;
[0147] Diaphragm preparation: The glass fiber film was punched into 16 mm diameter sheets as diaphragms;
[0148] Positive electrode preparation: A commercial 12 mm sodium sheet was used as the positive electrode;
[0149] Assembly: In a glove box filled with argon, stack the negative electrode shell, sodium sheet, electrolyte, diaphragm, electrolyte, negative electrode sheet, gasket, spring, and positive electrode shell in order, and seal them with a sealing machine. Before sealing, drip about 8uL of electrolyte, and then seal them in the battery shell to complete the battery assembly. The electrochemical performance of the assembled button battery is tested as follows:
[0150] Cycle performance test: constant current charge and discharge test method is adopted, the voltage test range is 0-3V, after 10 cycles at a current density of 0.1A / g, a long cycle performance test is performed at a current density of 2A / g. After 480 cycles, the capacity retention rate is calculated, capacity retention rate = 480th cycle discharge gram capacity / 11th cycle discharge gram capacity*100%.
[0151] 0.1A / g discharge capacity test: constant current charge and discharge test method is adopted, the voltage test range is 0-3V, the test current density is 0.1A / g, and the average discharge capacity of the negative electrode material in the first three times is calculated;
[0152] 2A / g discharge capacity test: constant current charge and discharge test method is adopted, the voltage test range is 0-3V, the test current density is 2A / g, and the average discharge capacity of the negative electrode material in the first three times is calculated;
[0153] ICE test (first coulomb efficiency): constant current charge and discharge test method is adopted to calculate the first coulomb efficiency at a voltage range of 0-3V and a current density of 0.1A / g. The first coulomb efficiency = first cycle charging capacity / first cycle discharging capacity.
[0154] The test results are shown in Table 1.
[0155] Table 1
[0156]
[0157]
[0158] From Table 1 we can at least see that:
[0159] (1) By comparing Examples 1-4 with Comparative Example 4, it can be seen that the negative electrode composite material provided by the present invention has a high pore volume by loading FeP and Fe7S8, and can serve as a channel for sodium ion deintercalation. As a negative electrode material for a sodium ion battery, it exhibits high gram capacity, high first coulombic efficiency and good rate performance, and has excellent long-cycle stability.
[0160] (2) By comparing Example 1 with Comparative Example 1, it can be seen that when only FeP is loaded on the waste cotton cloth-based carbon material, although the first coulombic efficiency is better, the discharge gram capacity is poor, and it is impossible to take into account both the first coulombic efficiency and the gram capacity at the same time.
[0161] (3) By comparing Example 1 and Comparative Example 2, it can be seen that when only Fe7S8 is loaded on the waste cotton cloth-based carbon material, the long-cycle stability performance is poor.
[0162] (4) By comparing Example 1 with Comparative Example 3, it can be seen that when the negative electrode material is a carbon material in which Fe3C is coated in waste cotton cloth, the first coulombic efficiency, gram capacity and long-cycle stability are significantly reduced.
[0163] (5) By comparing Example 1 with Comparative Example 5, it can be seen that when only one calcination is performed, the initial coulombic efficiency decreases significantly, especially the long-cycle stability performance decreases more significantly. The inventors found that the one-step calcination method is used. The results show that the FeP and Fe7S8 doped on the surface of the waste cotton cloth are unevenly distributed, which will affect the later cycle performance of the battery. The two-step calcination method first synthesizes the active material in the waste cotton cloth-based carbon-coated state, and then the two-step calcination makes the coated active material in situ converted into the FeP and Fe7S8 particle doping state more uniform. At the same time, it is not easy to control the temperature by directly synthesizing the composite material by one-step calcination.
[0164] (6) By comparing Example 1 with Comparative Example 6, it can be seen that when the magnetic boat containing sulfur powder, NaH2PO2 and the like are placed in sequence from the upstream to the downstream of the gas flow, .When the negative electrode material is prepared by the magnetic boat containing H2O and the magnetic boat containing the composite material, although the gram capacity and the first coulombic efficiency are better, the long cycle stability performance is significantly reduced. The inventors found that the preparation method provided in Comparative Example 6 will lead to a low FeP content in the negative electrode composite material and an excessive Fe7S8 content. The role of FeP in the composite material is to maintain the stability of the material, which is beneficial to the cycle stability of the material. If the Fe7S8 content is too high, the overall cycle performance of the material will be poor, and the long cycle stability performance of the negative electrode material obtained by the preparation method is worse than that when only Fe7S8 is loaded in Comparative Example 2, indicating that the preparation method itself will also reduce the long cycle stability performance of the negative electrode material; the preparation method provided in Example 1 of the present invention can ensure the uniformity of the doping of the phosphorus source and the sulfur source by adjusting the ratio of the phosphorus source and the sulfur source, thereby being able to take into account both the gram capacity and the long cycle stability performance.
[0165] In summary, the cotton fiber-based carbon composite material prepared according to the preparation method of the present invention has a lower specific surface area, and the powder also has a higher pore volume, which can serve as a channel for sodium ion deintercalation. Compared with the carbon material obtained by conventional cotton textile calcination, it has better ICE and high gram capacity and excellent rate performance.
[0166] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode composite material, characterized in that: The negative electrode composite material comprises a cotton fiber-based carbon material containing FeP and Fe7S8 on the surface.
2. The negative electrode composite material according to claim 1, characterized in that: The negative electrode composite material comprises a cotton fiber-based carbon material and FeP and Fe7S8 loaded on the cotton fiber-based carbon material; And / or, the negative electrode composite material is a sodium ion battery negative electrode composite material; And / or, in the negative electrode composite material, the mass fraction of FeP is 5% to 20%, and the mass fraction of Fe7S8 is 5% to 30%; And / or, the FeP is obtained by reacting a cotton fiber-based carbon / Fe3C composite material with a phosphorus source, the Fe7S8 is obtained by reacting a cotton fiber-based carbon / Fe3C composite material with a sulfur source, the reaction temperature is 500-700°C, the mass ratio of the cotton fiber-based carbon / Fe3C composite material, the phosphorus source and the sulfur source is 1:(1-20):(0.5-2), and the phosphorus source includes NaH2PO2 . at least one of H2O and red phosphorus, wherein the sulfur source comprises sulfur powder; And / or, the cotton fibers include waste cotton cloth.
3. A method for preparing the negative electrode composite material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: S1, soaking the cotton fiber in an alkaline solution, taking it out, and washing the cotton fiber with water until the pH value of the filtrate is in the range of 6-8; S2, soaking the cotton fiber treated in step S1 in an iron compound solution, shaking, taking out and drying for later use; S3, calcining the sample treated in step S2 under a protective gas atmosphere, and grinding to obtain a cotton fiber-based carbon / Fe3C composite material; S4. Put the cotton fiber-based carbon / Fe3C composite material into a small crucible, and put the small crucible into a large crucible containing a phosphorus source and a sulfur source, calcine under a protective gas atmosphere, and grind to obtain the negative electrode composite material.
4. The method for preparing the negative electrode composite material according to claim 3, characterized in that: In step S1, the cotton fiber is cut into small pieces with a length and width of 4cm*4cm-6cm*6cm and immersed in the alkaline solution for 30min-60min; and / or, in step S1, the mass of the cotton fiber is 2.5 g-3.5 g; And / or, the base includes at least one of sodium hydroxide and potassium hydroxide; And / or, the solid content of the alkaline solution is 10%-25%; And / or, in step S1, after the water washing, the cotton fiber is vacuum dried at a temperature of 90-120°C for 10-15 hours.
5. The method for preparing the negative electrode composite material according to claim 3, characterized in that: The iron-containing compound includes Fe(NO3)3; And / or, the concentration of iron ions in the iron-containing compound solution is 0.5 mol / L-2 mol / L; And / or, in step S2, a constant temperature oscillator is used for oscillation, the oscillation temperature is 20° C.-30° C., and the oscillation time is 8 h-24 h; And / or, in step S2, a vacuum drying oven is used for drying, the drying temperature is 60° C.-80° C., and the drying time is 12 h-24 h.
6. The method for preparing the negative electrode composite material according to claim 3, characterized in that: In step S3, the protective gas includes nitrogen; And / or, in step S3, the calcination includes heating to 600-900°C at a heating rate of 2-5°C / min and keeping the temperature for 2-4h.
7. The method for preparing the negative electrode composite material according to claim 3, characterized in that: In step S4, the phosphorus source and the sulfur source are located at different positions in the large crucible, and the stacking height of the phosphorus source and the sulfur source is not higher than the height of the small crucible; And / or, in step S4, the volume ratio of the small crucible to the large crucible is 1:3-1:4; And / or, the small crucible is not covered with a lid, and the large crucible is covered with a lid.
8. The method for preparing the negative electrode composite material according to claim 3, characterized in that: In step S4, the protective gas includes nitrogen, and the calcination includes heating to 500-700° C. at a heating rate of 2-5° C. / min and keeping the temperature for 4-8 hours; And / or, in step S4, the mass ratio of the cotton fiber-based carbon / Fe3C composite material, the phosphorus source and the sulfur source is 1:(1-20):(0.5-2).
9. A negative electrode plate, characterized in that: The negative electrode plate comprises: a negative electrode current collector layer; and A negative electrode material layer, wherein the negative electrode material layer is disposed on the surface of the negative electrode current collector layer, and the negative electrode material layer comprises the negative electrode composite material according to claim 1 or 2 or the negative electrode composite material prepared by the preparation method according to any one of claims 3-8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the negative electrode sheet according to claim 9.
Citation Information
Patent Citations
Preparation method of biomass-based graphitized carbon / Fe7S8 composite material
CN113036099A
Lithium ion battery negative electrode Fe7S8 / C composite material and preparation method and application thereof
CN115676900A
Plant carbon-supported metal compound nano composite material as well as preparation method and application thereof
CN115863569A
Fe7S8-FeP-C alkali metal ion battery negative electrode material and preparation and application thereof
CN118108263A
Cited By
Modified hard carbon material and preparation method thereof, negative pole piece and sodium ion battery
CN121247773A
